Use of platelet rich fibrin and Bio-OSS/SINT-Oss for implant-prosthetic rehabilitation in maxillary atrophy with sinus pathology: A 48-month follow-up. (April 2015) - Inchingolo, F; Ballini, A; Mura, SA; Farronato, D; Cirulli, N; Pettini, F; Gheno, E; Vermesan, D; Pederzoli, P; Resta, G; Caprio, M; Muollo, F; et al.
The maxillary sinus floor elevation procedure has gained popularity with predictable results, and is a safe, acceptable technique for bone augmentation, providing a base for dental implant treatment. Faint radiopaque lesions at the base of the maxillary sinus are frequent diagnoses on radiographs and must be identified during dental implant planning. The use of autografts, xenografts, allografts, and alloplasts or a combination between them has been demonstrated to be effective for increasing bone height and bone volume in maxillary sinus. The objective of this study was to evaluate the outcome of subjects with considerable sinus membrane pathology (test group) undergoing maxillary sinus floor augmentation using Platelet Rich Fibrin (PRF) as a filling material, in association with the Bio-Oss and Sint-Oss and simultaneous implant placement in a one-stage surgical procedure. All patients reported no pain to percussion, no sign of tissue suffering to the soft peri-implant tissues, the presence of an optimal primary stability of the inserted implants, and the increase in the peri-implant bone density. No complications were encountered during follow-up periods in these patients, including no negative evolution in the sinusitis and all implants are functioning successfully. In conclusion, the use of PRF and Piezosurgery reduced the healing time, favoring optimal bone regeneration and allowing sinus membrane integrity to be maintained during surgical procedures, according to evidence-based dentistry.